Retrospective Study of Renal Artery Doppler evaluation of Hypertensive patients - Paudel, Sharma; Ghimire, Ram Kumar; Panta, Om Biju; Pokharel, Ashbina (Nepalese Journal of Radiology, 2018)
Introduction: Doppler study is a good screening test for initial screening of renal artery stenosis however controversies exists regarding its use as screening study. This study aims to evaluate the Doppler study findings in patients with atypical hypertension. Methods: The study was a retrospective hospital record based study conducted in Metro Radiological and Imaging Center, Kathmandu. Reports of Doppler studies performed for atypical hypertension were reviewed for the duration of 6 years (2009 to 2014). Doppler studies were performed by two experienced radiologist with more than 5 and 20 years of experience. Patients with transplant kidney, patient with accessory renal artery and patient with known chronic kidney disease were excluded from the study. Data was entered in predesigned proforma and analysis was done with SPSS 21.0. Results: A total of 1001 Doppler studies done during the study period revealed abnormalities in 227 patients. The most common abnormality was elevation of main renal artery and lobar renal artery resistance index, alone which was seen in 187(82.4%) patients. Renal artery stenosis was noted in 30(13.2%) cases with 10 patients each having renal artery stenosis involving left and right renal arteries respectively and 10 patients had bilateral renal artery stenosis. Conclusion: Non-specific raised resistance index indicating renal impairment is the most common abnormality in atypical hypertensives. The presence of renal artery stenosis in atypical hypertensive is around 3%.